The abundance and characteristics of microplastics in surface water in the transboundary Ganges River. (1st April 2021) - Napper, Imogen E.; Baroth, Anju; Barrett, Aaron C.; Bhola, Sunanda; Chowdhury, Gawsia W.; Davies, Bede F.R.; Duncan, Emily M.; Kumar, Sumit; Nelms, Sarah E.; Hasan Niloy, Md Nazmul; Nishat, Bushra; Maddalene, Taylor; et al.
Abstract: Microplastics (plastic < 5 mm in size) are now known to contaminate riverine systems but understanding about how their concentrations vary spatially and temporally is limited. This information is critical to help identify key sources and pathways of microplastic and develop management interventions. This study provides the first investigation of microplastic abundance, characteristics and temporal variation along the Ganges river; one of the most important catchments of South Asia. From 10 sites along a 2575 km stretch of the river, 20 water samples (3600 L in total) were filtered (60 samples each from pre- and post-monsoon season). Overall, 140 microplastic particles were identified, with higher concentrations found in the pre-monsoon (71.6%) than in post-monsoon (61.6%) samples. The majority of microplastics were fibres (91%) and the remaining were fragments (9%). We estimate that the Ganges, with the combined flows of the Brahmaputra and Meghna rivers (GBM), could release up to 1–3 billion (10 9 ) microplastics into the Bay of Bengal (north-eastern portion of the Indian Ocean) every day. This research provides the first step in understanding microplastic contamination in the Ganges and its contribution to the oceanic microplastic load. Graphical abstract: Image 1 Highlights: The microplastics identified were dominated by fibers (91%) and fragments (9%). A greater number of microplastics were found pre-monsoon than post-monsoon Microplastic concentrations increased from source to sea. Approximately 1–3 billion microplastic pieces are discharged into the Bay of Bengal daily. Abstract : We estimate that up to 1–3 billion microplastics are released into the Bay of Bengal every day.